The Beneficial Role of Retinoids in Glomerular Disease - Mallipattu, Sandeep K.; He, John Cijiang (Frontiers in Medicine, 2015)
The primary etiology of CKD is a direct consequence of initial dysfunction and injury of the glomerulus, the main filtration system. Podocytes are terminally differentiated epithelial cells in the glomerulus, whose major function is the maintenance of this renal filtration barrier. Podocyte injury is implicated in many glomerular diseases including Focal Segmental Glomerular Sclerosis (FSGS) and HIV-associated nephropathy (HIVAN). In many of these diseased conditions, the podocyte can either undergo dedifferentiation and proliferation, apoptosis, or cell detachment. Regardless of the initial type of injury, the podocyte ultimately loses its functional capacity to maintain the glomerular filtration barrier. Significant injury resulting in a loss of the podocytes and failure to maintain the renal filtration barrier contributes to progressive kidney disease. Consequently, therapies that prevent podocyte injury and promote their regeneration will have a major clinical impact on glomerular disease. Retinoic acid (RA), which is a derivative of vitamin A, has many cellular functions including induction of cell differentiation, regulation of apoptosis, and inhibition of inflammation and proliferation. RA is required for kidney development and is essential for cellular differentiation in the setting of podocyte injury. The mechanism by which RA directs its beneficial effects is multifactorial, ranging from its anti-inflammatory and anti-fibrotic effects to a direct effect of upregulating podocyte differentiation markers in the podocyte. The focus of this review is to provide an overview of RA in kidney development and glomerular disease. We also highlight the key mechanism(s) by which RA restores podocyte differentiation markers and ameliorates glomerular disease.